Child Homicide: A Global Public Health Concern. - Delan Devakumar; David Osrin (PLoS Medicine)
In this perspective, Delan Devakumar and David Osrin discuss Abrahams and colleagues' findings in the context of evidence about child homicide in different countries, and consider etiology along with implications for child protection and prevention.